2010
DOI: 10.1186/1471-2407-10-177
|View full text |Cite
|
Sign up to set email alerts
|

In vivo tumor cell adhesion in the pulmonary microvasculature is exclusively mediated by tumor cell - endothelial cell interaction

Abstract: BackgroundMetastasis formation is the leading cause of death among colon cancer patients. We established a new in-situ model of in vivo microscopy of the lung to analyse initiating events of metastatic tumor cell adhesion within this typical metastatic target of colon cancer.MethodsAnaesthetized CD rats were mechanically ventilated and 106 human HT-29LMM and T84 colon cancer cells were injected intracardially as single cell suspensions. Quantitative in vivo microscopy of the lung was performed in 10 minute int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 52 publications
1
43
0
2
Order By: Relevance
“…This occurs through adhesive interactions between cancer cells and endothelial cells involving some cell adhesion proteins like integrins, selectins and members of the immunoglobulin superfamily. 22 The next important phase is invasion of the tumor cells through the endothelial cell layer, neighboring basement membrane (this process is called extravasation), and target organ tissue. Then there is step of development of secondary tumor foci at the distant organ.…”
Section: Metastasismentioning
confidence: 99%
“…This occurs through adhesive interactions between cancer cells and endothelial cells involving some cell adhesion proteins like integrins, selectins and members of the immunoglobulin superfamily. 22 The next important phase is invasion of the tumor cells through the endothelial cell layer, neighboring basement membrane (this process is called extravasation), and target organ tissue. Then there is step of development of secondary tumor foci at the distant organ.…”
Section: Metastasismentioning
confidence: 99%
“…2). At this time, endothelial ICAM-1 is involved in tumor cell adhesion to the endothelium; this is a particularly important phenomenon considering that tumor adherence to vessel walls is a common feature across numerous types of cancer (51). Ghislin et al reported that ICAM-1 expressed on the surface of endothelial cells is crucial for the adhesion of melanoma cells to the endothelial monolayer in vitro.…”
Section: Tumor Cell Adhesion: Lending Tumor Cells a Handmentioning
confidence: 99%
“…Recent studies have shown that CTCs from many types of primary tumors express sialylated carbohydrate ligands similar to leukocytes, which mediate interactions with selectins on the endothelium (5,6). Selectins possess rapid, force-dependent binding kinetics, which can trigger the rolling adhesion of CTCs along the blood vessel wall (7,8). CTCs can subsequently transition from rolling to firm adhesion, allowing for transendothelial migration into tissues and eventual formation of micrometastases (9).…”
mentioning
confidence: 99%